Kedudukan Harta Bersama Perkawinan Poligami - Arif Zunaidi (Institut Agama Islam Negeri (IAIN) Kediri, 2018)
Islam allows the marriage of more than one partner, provided that the husband can be fair and getpermission from the first wife. As a result of polygamous marriages, there is legal uncertainty aboutjoint assets, both in the first, second, third and fourth wives. The purpose of this paper is to find out thelegal certainty of shared assets in polygamous marriages. The method used is a normative legal researchmethod, using a regulatory approach, both Islamic law, Law Number 1 of 1974 and KHI. As a result, thereis legal uncertainty especially for the first wife based on the Compilation of Islamic Law, specifically legalprotection for the property with the wife brought in by her husband’s second marriage. According to LawNo. 1 of 1974, each wife gets a second share, whereas according to Islamic law the status of a woman’sproperty does not change with the marriage.